Abdominal crunch exercise analysis performed with maximum and submaximum loads: An electromyographic study - M.L. Moura; L.S. Tessutti; A.C. Moraes (Desafio Singular, 2011)
The purpose of this study was to verify the electromyographic activity of the rectus abdominis and obliquus externus abdominis during abdominal crunch exercise performed with maximum and submaximum loads. Thirteen male and female university students participated in this investigation (18-23 years old). The subjects completed abdominal crunch exercise until exhaustion with 20, 40, 60 and 80% of the maximum load. The root-mean-square (RMS) from electromyography activity of the rectus abdominis and obliquus externus muscles from the first and last three repetitions from each workload performed was analyzed. RMS for the last repetitions increased in relation to the first repetitions for the 20% workload, first two repetitions on 40% workload and first repetition on the 80% workload. There was no difference for the 60% workload. Results showed that external load on abdominal crunch exercise might be an alternative to increase intensity while performing abdominal crunch exercise, which on its turn can be a practical tool for subjects that aim to increase abdominal strength level.